Material science of in-directly expanded α (1,4) and (1,6) linked polymers - Davies, Suzanne (2017)
This research utilises twin-screw extruded directly expanded maize grits (IP1) into a secondary extrusion process, to create a homogenous intermediate product microstructure; that is later expanded into a final product using hot oil. The aim of this research is to begin to link ingredient processing to intermediate and final product microstructures and understand how this effects final product attributes.